2010
DOI: 10.1620/tjem.222.251
|View full text |Cite
|
Sign up to set email alerts
|

TNF-.ALPHA. in Hypothalamic Paraventricular Nucleus Contributes to Sympathoexcitation in Heart Failure by Modulating AT1 Receptor and Neurotransmitters

Abstract: Proinflammatory cytokines, including tumor necrosis factor (TNF)-α , augment the progression of heart failure (HF) that is characterized by sympathoexcitation. In this study, we explored the role of TNF-α in hypothalamic paraventricular nucleus (PVN) in the exaggerated sympathetic activity observed in HF. Heart failure rats were made by ligating the left anterior descending coronary artery. The expression levels of angiotensin type 1 receptor (AT1-R) and neurotransmitters were analyzed in the PVN of HF rats th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 45 publications
(94 reference statements)
1
40
1
Order By: Relevance
“…Although etanercept is too large a molecule for all but a small amount of a subcutaneous (s.c.) dose to enter the cerebrospinal fluid (CSF), intentionally compensating for this by giving a 20-fold larger dose reduces brain glutamate in a rat model of traumatic brain injury [117]. Etanercept has also been reported, in a heart failure model in which TNF is increased [118, 119], to lower rat brain glutamate dramatically when given intracerebroventricularly (i.c.v), although, again because of its high molecular weight, not when administered intraperitoneally (i.p. ).…”
Section: Glutamate Toxicity As a Major Manifestation Of Excess Tnf Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although etanercept is too large a molecule for all but a small amount of a subcutaneous (s.c.) dose to enter the cerebrospinal fluid (CSF), intentionally compensating for this by giving a 20-fold larger dose reduces brain glutamate in a rat model of traumatic brain injury [117]. Etanercept has also been reported, in a heart failure model in which TNF is increased [118, 119], to lower rat brain glutamate dramatically when given intracerebroventricularly (i.c.v), although, again because of its high molecular weight, not when administered intraperitoneally (i.p. ).…”
Section: Glutamate Toxicity As a Major Manifestation Of Excess Tnf Inmentioning
confidence: 99%
“…This is evolutionarily essential because of the key role of this amino acid in the synaptic cleft, where it is responsible for the fast excitatory neurotransmission necessary for the rapid brain responses demanded for survival in the real world. Thus, given the role of TNF to influence both glutaminase and re-uptake proteins described earlier, the capacity of intracerebral etanercept to lower brain glutamate, as summarized above [117119], can be expected to act with somewhat the same degree of rapidity. It seems likely, therefore, that these data rationalize the unexpected but clearly rapid response in case reports and open trials to perispinal etanercept, initially reported in 2003 [121] and 2008 [122], and regularly confirmed since [123127].…”
Section: Do These Actions Of Tnf Explain the Rapid Response To Etanermentioning
confidence: 99%
“…The method for PVN minipump has been previously described82627. Each rat head was placed into a stereotaxic apparatus after anesthetized with ketamine (90 mg/kg) and xylazine (10 mg/kg) intraperitoneally (i.p).…”
Section: Methodsmentioning
confidence: 99%
“…Maximum renal sympathetic nerve activity (RSNA) was detected using an intravenous bolus administration of sodium nitroprusside (SNP, 10 mg). The recordings of rectified and integrated RSNA were analyzed using methods described as previously826.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis that the hypothalamus plays a crucial role in both reduced food intake and cachectic body wasting is supported by a combination of findings. Firstly, neuroinflammation and disturbed hypothalamic signalling is present in cachectic chronic diseases such as cancer [5], HIV [26,27], COPD [28] and heart failure [29,30]. Secondly, the hypothalamus has the highest density of receptors for these pro-inflammatory cytokines in the brain [31].…”
Section: Hypothalamic Inflammationmentioning
confidence: 99%